Transcutaneous measurement of bilirubin by icterometer during phototherapy on a bilibed - (:unkn) unknown (My University, 2002)
AIM: We aimed to find the correlation between bilirubin levels measured spectrophotometrical]y and transcutaneously by an icterometer and investigate if the number of serum bilirubin measurements can be reduced by using an icterometer during phototherapy on a bilibed. METHODS: The study group consisted of 52 babies with total serum bilirubin values less than 18 mg/dl, who were treated by phototherapy at the bilibed in the Neonatology Unit of Marmara University Hospital. Eighty-nine measurements were made from the study population. During phototherapy on the bilibed, the face of the baby was not affected by phototherapy light, allowing transcutaneous bilirubinometry to be more accurate. Serum bilirubin was measured spectrophotometrically on capillary blood in all subjects. A simultaneous transcutaneous bilirubin measurement with the icterometer was done by a pediatrician who was blind to the serum bilirubin levels. RESULTS: The mean gestational age was 38±2.2 (34-41) weeks, birth weight 2979±505 (1500-3900) g and the serum bilirubin of the study group was 14.9±1.6 (10.4-18) mg/dl. Although the comparison of the icterometric measurements and the serum bilirubin levels showed a statistically significant relation (p<0.0001) in the whole group, the correlation was moderately strong (r=0.59). The correlation was weaker in infants whose bilirubin levels were more than 15 mg/dl (r =0.32). CONCLUSION: We concluded that spectrophotometric bilirubin measurements cannot be replaced by measurements obtained transcutaneously from babies whose bilirubin values are more than 15 mg/dl.
Keywords: Bilibed; Hyperbilirubinemia; Icterometer